Inhibiting geranylgeranyl diphosphate synthesis reduces nuclear androgen receptor signaling and neuroendocrine differentiation in prostate cancer cell models. Issue 1 (14th August 2018) - Weissenrieder, Jillian S.; Reilly, Jacqueline E.; Neighbors, Jeffrey D.; Hohl, Raymond J.
Abstract : Background: Following androgen deprivation for the treatment of advanced adenocarcinoma of the prostate, tumors can progress to neuroendocrine prostate cancer (NEPC). This transdifferentiation process is poorly understood, but trafficking of transcriptional factors and/or cytoskeletal rearrangements may be involved. We observed the role of geranylgeranylation in this process by treatment with digeranyl bisphosphonate (DGBP), a selective inhibitor of geranylgeranyl pyrophosphate synthase which blocks the prenylation of small GTPases such as Rho and Rab family proteins, including Cdc42 and Rac1. Methods: We examined the therapeutic potential of DGBP in LNCaP, C4‐2B4, and 22Rv1 cell culture models. Cell morphology and protein expression were quantified to observe the development of the neuroendocrine phenotype in androgen‐deprivation and abiraterone‐treated LNCaP models of NEPC development. Luciferase reporter assays were utilized to examine AR activity, and immunofluorescence visualized the localization of AR within the cell. Results: Essential genes in the isoprenoid pathway, such as HMGCR, MVK, GGPS1, and GGT1, were highly expressed in a subset of castration resistant prostate cancers reported by Beltran et al. Under treatment with DGBP, nuclear localization of AR decreased in LNCaP, 22Rv1, and C4‐2B4 cell lines, luciferase reporter activity was reduced in LNCaP and 22Rv1, and AR target gene transcription also decreased in LNCaP. Conversely, nuclear localization of AR was enhanced by the addition of GGOH. Finally, induction of the NEPC structural and molecular phenotype via androgen deprivation in LNCaP cells was inhibited by DGBP in a GGOH‐dependent manner. Conclusions: DGBP is a novel compound with the potential to reduce AR transcriptional activity and inhibit PCa progression to NEPC phenotype. These results suggest that DGBP may be used to block cell growth and metastasis in both hormone therapy sensitive and resistant paradigms.